Genesis, Development and Popularization of Doctor of Pharmacy (PharmD) Education Program at the Global level - A study based on the story from 1955 to 2009. - K.G, Revikumar; G.P, Mohanta.; R, Veena; Sekhar, Sonal (Indian Journal of Pharmacy Practice)
The concept of clinical pharmacy was introduced in pharmacy profession by the American Hospital pharmacists during the period 1920-1940, though the term 'clinical pharmacy' as such was not coined during those days. Clinical pharmacy as discipline evolved in USA from a combination of factors that contributed for the development and achievements in the area of hospital pharmacy. The introduction of PharmD in the University of California at San Francisco in 1955 contributed for the overall growth and popularization of clinical pharmacy. By 1980s the PharmD became a sought after course in the US. The American Association of College of Pharmacy (AACP) and the Accreditation Council for Pharmaceutical Education adopted PharmD as the essential and basic qualification required for the practice of pharmacy. Along with the regular PharmD, other non-traditional programs like post baccalaureate PharmD were also introduced and PharmD got migrated to other parts of the world. When the Foreign Pharmacy Graduation Equivalency Committee (FPGEC) in the US mandated a 5 year pharmacy graduation program to be eligible to the Foreign Pharmacy Graduation Equivalency Examination ( FPGEE), pharmacists from other countries particularly Asian countries including India got upset. All this prompted Indian authorities too to think of introducing PharmD. Finally the PharmD program was initiated in India in 2008 in few selected institutions approved by the Pharmacy Council of India. In spite of the limitations of the Indian PharmD structure and the curriculum, the program will develop to one of the best such programs in the world in the years to come.
Keywords: PharmD; Doctor of Pharmacy; Pharmacy Practice; PharmDr